Odpowiedź:
[tex]\frac{3}{2\sqrt{7} } = \frac{3*\sqrt{7} }{2*\sqrt{7} *\sqrt{7} }[/tex] = [tex]\frac{3\sqrt{7} }{14}[/tex]
[tex]\frac{9}{2\sqrt{3} }[/tex] = [tex]\frac{9*\sqrt{3} }{2\sqrt{3}*\sqrt{3} }[/tex] = [tex]\frac{9\sqrt{3} }{6} = \frac{3\sqrt{3} }{2}[/tex]
Szczegółowe wyjaśnienie:
[tex]\frac{3}{2\sqrt{7} } = \frac{3*\sqrt{7} }{2*\sqrt{7} *\sqrt{7} }[/tex] = [tex]\frac{3\sqrt{7} }{14}[/tex]
[tex]\frac{9}{2\sqrt{3} }[/tex] = [tex]\frac{9*\sqrt{3} }{2\sqrt{3}*\sqrt{3} }[/tex] = [tex]\frac{9\sqrt{3} }{6} = \frac{3\sqrt{3} }{2}[/tex]